Expression of genes and proteins of the pax‐six‐eya‐dach network in the metamorphic sea urchin: Insights into development of the enigmatic echinoderm body plan and sensory structures. Issue 1 (9th November 2017) - Byrne, Maria; Koop, Demian; Morris, Valerie B.; Chui, Juanita; Wray, Gregory A.; Cisternas, Paula
Abstract : Background: Photoreception‐associated genes of the Pax‐Six‐Eya‐Dach network (PSEDN) are deployed for many roles in addition to photoreception development. In this first study of PSEDN genes during development of the pentameral body in sea urchins, we investigated their spatial expression in Heliocidaris erythrogramma .Results: Expression of PSEDN genes in the hydrocoele of early ( Dach, Eya, Six1/2 ) and/or late ( Pax6, Six3/6 ) larvae, and the five hydrocoele lobes, the first morphological expression of pentamery, supports a role in body plan development. Pax6, Six1/2, and Six3/6 were localized to the primary and/or secondary podia and putative sensory/neuronal cells. Six1/2 and Six3/6 were expressed in the neuropil region in the terminal disc of the podia. Dach was localized to spines. Sequential up‐regulation of gene expression as new podia and spines formed was evident. Rhabdomeric opsin and pax6 protein were localized to cells in the primary podia and spines.Conclusions: Our results support roles for PSEDN genes in development of the pentameral body plan, contributing to our understanding of how the most unusual body plan in the Bilateria may have evolved. Development of sensory cells within the Pax‐Six expression field is consistent with the role of these genes in sensory cell development in diverse species. Developmental Dynamics 247:239–249, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Genes of the Pax‐Six‐Eya‐Dach developmental GRN (PSEDN) are involved in development of the metamorphic sea urchin. In situ localization of PSEDN genes in the hydrocoele lobes, the first morphological expression of pentamery, indicates a role in development of this most unusual bilaterian body plan. Sequential up regulation of gene expression as new podia and spines form indicate a metameric‐like pattern. Expression of Pax6, Six 1/2 and Six 3/6 in putative photosensory cells is consistent with the role of these genes in development of photosensory cells, as is localization of opsin, histamine receptor and pax6 protein.